Pedal power measurement as a diagnostic tool for functional vascular problems. (January 2019) - Kleinloog, Jordi P.D.; van Hooff, Martijn; Savelberg, Hans H.C.M.; Meijer, Eduard J.; Schep, Goof
Abstract: Background: Cyclists with flow limitations in the iliac arteries complain of pain and loss of power. To investigate whether pedal power measurement has added value in diagnosing the underlying cause of flow limitations in the iliac arteries, we explored the sensitivity and specificity of various pedal power measurement variables. Moreover, it was assessed what the added value of pedal power measurement is compared to diagnosis based on the conventional ankle-brachial blood pressure index. Methods: 25 healthy participants and 45 patients with unilateral arterial flow limitations were recruited. Participants received Echo-Doppler examination to determine the condition of the iliac arteries. Subsequently, participants performed a maximal cycle ergometer test. During the cycling test the exerted left and right pedal power was measured. From these measurements several variables were derived to diagnose arterial flow limitations. A receiver operating characteristics curve based on a predicted cross-validated model was used to select the variable with the highest predictive value and its cut-off value. Findings: The mean power difference between both legs relative to the exerted power at 95% of the maximal power showed the best predictive value with a sensitivity of 0.76 and a specificity of 0.88. Combining the pedal power measurement and ankle-brachial blood pressure index resulted in a sensitivity of 0.91 and a specificity of 0.88. Interpretation: Pedal power measurement improves sensitivity of diagnosis of iliac artery flow limitations, without increasing the burden of clinical investigation to the patients. Highlights: Vascular problems are often not recognised, since current tests lack sensitivity. Cyclists with vascular problems complain about loss of power in the affected leg. Pedal power was measured for both legs independently during exercise testing. Receiver operating characteristic including a cross-validation model was performed. Pedal power measurement is a useful additional tool to diagnose vascular problems.